Opinion 2472: Circus assimilis Jardine & Selby, 1828 and Circus approximans Peale, 1848 (Aves, Accipitriformes): usage conserved - ICZN (Bulletin of Zoological Nomenclature, 2021)
The International Commission on Zoological Nomenclature has conserved current usage of the specific name of Circus assimilis Jardine & Selby, 1828 for the Australo-Wallacean spotted harrier by designating a neotype for this nominal species. The International Commission on Zoological Nomenclature has also conserved current usage of the specific name of Circus approximans Peale, 1848 by suppressing, for the purposes of the Principle of Priority, its objective synonym Circus juxta Peale, 1848, which was published simultaneously with it but was designated as the senior synonym by the first reviser.